Examining Public Concern about Global Warming and Climate Change in China. (8th June 2020) - Liu, Xinsheng; Hao, Feng; Portney, Kent; Liu, Yinxi
Abstract: To what degree are Chinese citizens concerned about the seriousness of global warming and climate change (GWCC) and what are the key factors that shape their concern? Drawing theoretical insights from extant literature and using recent data from a national representative public survey (N = 3, 748) and provincial environmental and economic statistics, this study, the first of its kind, examines the variations and determinants of Chinese GWCC concern. Our data show that in China, compared to other countries, average public concern about GWCC is relatively low, and concern varies greatly among Chinese citizens, across different provinces and between coastal and inland areas. Statistical analyses reveal that the levels of Chinese GWCC concern are significantly influenced by individual sociodemographic characteristics, personal post-materialist values, and regional economic dependency on carbon-intensive industries. Specifically, women and younger Chinese with greater post-materialist values are more concerned about GWCC than their counterparts, and citizens from provinces with higher economic dependency on carbon-intensive industries tend to be less concerned about GWCC than people from provinces with lower carbon dependency. We discuss key policy implications and make suggestions for future research in the conclusion.